2002
DOI: 10.1099/00221287-148-4-1183
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a nonpigmented mutant of Porphyromonas gingivalis: cell surface polysaccharide as an anchorage for gingipains The GenBank/EMBL/DDBJ accession number for the sequences reported in this paper is D64132.

Abstract: A nonpigmented mutant of Porphyromonas gingivalis was constructed by using transposon mutagenesis. The mutant possessed the transposon DNA at the novel gene porR. Gene targeted mutagenesis revealed that porR was responsible for pigmentation. The porR gene shared similarities with genes of the degT family, the products of which are now considered to be transaminases involved in biosynthesis of sugar portions of cell-surface polysaccharides and aminoglycosides. The porR mutant showed a pleiotropic phenotype : de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 47 publications
5
134
0
Order By: Relevance
“…3A). The absence of gingipains in the OM of the waaL Ϫ mutant strain may be a consequence of a defect in gingipain OM anchoring mechanisms, as reported in a porR mutant (26). SDS-PAGE and Western blot analysis of the OM showed equivalent amounts of RagA/B in the four strains (Fig.…”
Section: Lps O Antigens Are Not Essential For Omv Biogenesis-mentioning
confidence: 84%
See 2 more Smart Citations
“…3A). The absence of gingipains in the OM of the waaL Ϫ mutant strain may be a consequence of a defect in gingipain OM anchoring mechanisms, as reported in a porR mutant (26). SDS-PAGE and Western blot analysis of the OM showed equivalent amounts of RagA/B in the four strains (Fig.…”
Section: Lps O Antigens Are Not Essential For Omv Biogenesis-mentioning
confidence: 84%
“…3, A and B, lane 4, and supplemental Table S2). Previously it has been reported that the porR locus is not only required for A-LPS formation but also for gingipain glycosylation and maturation: certain glycan moieties are common to these glycosylated proteases and to A-LPS (15,20,26). If RagA/B were gingipain substrates, the presence of RagA/B in the OMV purified from porS Ϫ and the waaL Ϫ strains might simply reflect reduced gingipain activity in those strains rather than the absence of a specific sorting mechanism.…”
Section: Lps O Antigens Are Not Essential For Omv Biogenesis-mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our findings are significant, as they indicate upregulation of adhesins that in turn facilitate initial adhesion and allow colonization of the oral cavity. On the other hand, PG1138, encoding the major pigmentation and extracellular proteinase activity regulator PorR, was downregulated (Table 2) (Shoji et al, 2002). This regulator has been demonstrated to play a role in modulating the activity of the major group of P. gingivalis proteases, including Rgp and Kgp (Curtis et al, 2001).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Given that these two virulence factors, independently of each other, can be potent immune effectors in the host, why has P. gingivalis acquired this co-operation with its LPS and Arg gingipains as well? Experiments conducted with deletion mutants in the loci porR (PG1138) and wbpB (PG2119), which are devoid of A-LPS but possess O-LPS [59,60], exerted less gingipain enzymatic activity. These loci are, therefore, probably involved in the biosynthesis of A-LPS [60,61].…”
Section: A-lps Provides Serum Resistance To P Gingivalismentioning
confidence: 99%